1999
DOI: 10.5803/jsfm.16.221
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Fermented Soybean Product "Natto" on the Composition and Metabolic Activity of the Human Fecal Flora.

Abstract: The effects of the fermented soybean product "Natto" on the composition and metabolic activity were studied in seven healthy volunteers (22-49 years of age) who ingested 50g of Natto/day for 14 days. During Natto consumption, the counts of Bacillus subtilis (B. natto; p<0.001) and Bifidobacterium (p<0.05) were significantly increased, except for the numbers of Bifidobacterium in two volunteers, whereas the counts and the frequency of occurrence of lecithinase-positive clostridia (p<0.05), including Clostridium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…Previous research has suggested that the consumption of fermented foods increases the abundance of Bifidobacterium and decreases that of Clostridium (49). Moreover, the intake of fermented foods, such as natto, was related to gut microbiota composition, particularly an increased relative abundance of Bifidobacterium (50). We infer that the high relative abundance of Bifidobacterium observed in Japanese people may result from the habitual consumption of traditional Japanese fermented foods (e.g.…”
Section: Discussionmentioning
confidence: 78%
“…Previous research has suggested that the consumption of fermented foods increases the abundance of Bifidobacterium and decreases that of Clostridium (49). Moreover, the intake of fermented foods, such as natto, was related to gut microbiota composition, particularly an increased relative abundance of Bifidobacterium (50). We infer that the high relative abundance of Bifidobacterium observed in Japanese people may result from the habitual consumption of traditional Japanese fermented foods (e.g.…”
Section: Discussionmentioning
confidence: 78%
“…This effect might have been caused by an improvement in the growth of Lactobacillus, caused by B. subtilis (Yang et al, 2015). The intake of natto was shown to improve the composition of Bifidobacterium in fecal flora (Terada et al, 1999). However, it has also been reported that the intake of natto did not affect the composition of intestinal Bifidobacterium, and could not improve constipation (Takemura et al, 2009).…”
Section: Introductionmentioning
confidence: 91%
“…It has been reported that miso could act as a chemopreventive agent for colon carcinogenesis (Masaoka et al 1998;Ohara et al 2002). It was shown that the consumption of raw natto led to an improvement in the intestinal environment, for example, a decrease in the content of ammonia, sulphide, pH, putrefactive products, and the counts of clostridia and Enterobacteriaceae, while an increase in the counts of bifidobacteria, lactobacilli and faecal short-chain fatty acids was observed (Terada et al 1999). Fujisawa et al (2006) also investigated the effect of miso soup containing natto on the composition and metabolic activity of the human faecal microbiota, and indicated that the number of Bacillus and Bifidobacterium increased and the number of Enterobacteriaceae decreased, and lecithinase-positive clostridia including C. perfringens tended to decrease during intake.…”
Section: Non-fermented Soybean Milkmentioning
confidence: 97%